Materi Khitan sebagai Sarana Pendidikan Seks pada Mata Pelajaran Fikih MI - Fatiya Sakinah; Rahma Annisa; Rahmah Desfitria; Winda Nur Febrianti; Andi Prastowo (AN NUR: Jurnal Studi Islam, 2021)
Islam is a religion that always teaches cleanliness.  In a saying, Rasulullah SAW stated: "purification is half of faith". One of the Islamic laws in maintaining cleanliness is circumcision.  In this research, we will study about sex education in the material of circumcision at Madrasah Ibtidaiyah.  The research method used is library research by referring to the literature that supports this research.  The teaching of circumcision material at MI includes the history of the circumcision requirement, its meaning, the objectives and benefits, the law of circumcision, the time for circumcision, and finally the wisdom of circumcision.  Then in this study will be seen to what extent the teaching of sex education to children in the material of circumcision jurisprudence.  So that with this, it is hoped that parents or teachers can apply appropriate sex education teaching to children, both in terms of age and psychological development.